ФІБРОЗНО-КІСТОЗНА МАСТОПАТІЯ У ЖІНОК РЕПРОДУКТИВНОГО ВІКУ: ДИСФУНКЦІЯ ЯЙНИКІВ - Галишич, Н. М. (Українські медичні вісті, 2023)
ФІБРОЗНО-КІСТОЗНА МАСТОПАТІЯ У ЖІНОК РЕПРОДУКТИВНОГО ВІКУ: ДИСФУНКЦІЯ ЯЙНИКІВ